INTER-RELIGIOUS RELATION ACCORDING TO FIQH OF PESANTREN: A STUDY FROM BAHSUL MASAIL OF MA’HAD ALY SALAFIYYAH SYAFI’IYYAH SITUBONDO - Ikhsanudin, Muhammad (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2023)
This article focuses on the views and dynamics of thought among the students at the Situbondo Islamic Boarding School. The research was conducted at Ma’had Aly Islamic Boarding School Salafiyyah Syafi’iyyah Situbondo, a productive Islamic boarding school publishing legal opinions and becoming a barometer in the East and Madura region. This study examines the issues of inter-religious relations reflected in the students’ legal arguments. The research is a qualitative study with a primary focus on a literature review of the legal views published by the boarding school, supported by semi-structured interviews. The research material is the legal opinions of the boarding school. The primary source of the research is published legal arguments, while the secondary source is books or other academic works related to the central theme of the study, which is the history of Islamic boarding schools, inter-religious relations, and models of legal discovery. The research results at Situbondo’s Ma’had Aly Islamic Boarding School show a more liberal perspective in addressing inter-religious issues. Ma’had Aly allows non-Muslim leaders and marriages to members of other religions and applies a method of legal discovery supported by istimbath istislahi and kulliyah principles. Both show that Ma’had Aly has a more open and inclusive perspective in addressing inter-religious issues.